Los alimentos de calidad diferenciada: una herramienta para el desarrollo rural sostenible - Tolón Becerra, Alfredo; Lastra Bravo, Xavier (M+A. Revista Electrónica de Medioambiente, 2009)
This article analyzes the food quality certification as a sustainable development tool in rural areas of Europe and Spain. First, brief introduction about the quality policies of agro-food products in relation to European rural development carry out. Later, different labels for many food products, legislation, and its evolution at European and Spanish level are characterized. Then, the future perspectives of the labels are analyzed, through a study of case in Los Vélez county (Almería), where is made: a diagnosis of the current status of agricultural and livestock production, an analysis of certification processes and their difficulties, and set out future actions of implementation of new quality certification labels that support the development of the region. Finally, like conclusion, the beneficial effects of labels on several of the principles of sustainable rural development are highlighted.